Nutrition substance of Thunnus sp. as an alternative to improving community nutrition - Andi Syamsiah Adha; Suriyanti Suriyanti; Fatmawaty Mallapiang (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Thunnus sp. (Tuna fish) is a group of fish which is the main export commodity of sea fish consumed from Indonesia. Tuna is one type of sea fish that has high protein levels. This study aims to determine the nutrient content (water content, ash content, carbohydrate, protein, fat, and iron (Fe), bacterial and mold microorganism test, organoleptic test, and P <0.05 friedmen test on tuna meat flour. The design in this study was experimental with a pre-experimental One-Shot Case Study design with the treatment of tuna meat flour drying.The results of the study with replication three times showed that the average water content was 8.37%, ash content was 3.86% , 3.99% carbohydrates, 71.45% protein, 9.45% fat, and 1.49 μg / g Fe. Microorganism test on bacteria for all 3 treatments was all safe. In addition there was an influence on the quality of tuna meat flour from aspects of color, aroma, texture. Therefore drying tuna meat flour at a temperature of 60 ° C is the best product that is fit for consumption as an additional food to meet the nutritional needs of the community every day.